2018
DOI: 10.1002/app.46183
|View full text |Cite
|
Sign up to set email alerts
|

Design of thermosetting polymeric systems based on benzoxazines modified with maleic anhydride

Abstract: A novel benzoxazine (BzPFA) with carboxylic acid groups in its structure was synthesized in a two-step process. First, BzPOH monomer was obtained from bisphenol A, paraformaldehyde, and ethanolamine with an initial molar ratio 1:4:2. Then, BzPOH was reacted with maleic anhydride using a stoichiometric 1:1 ratio of oxazine ring:maleic anhydride to produce a mixture of oligomeric species named BzPFA. The products were characterized by nuclear magnetic resonance, size-exclusion chromatography, and Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[ 1–5 ] Polybenzoxazine precursors are synthesized via one stage Mannich‐like condensation from a phenol derivative, formaldehyde, and a primary amine in a stoichiometric molar ratio of 1:2:1. [ 6–9 ] As benzoxazine chemistry offers high molecular design flexibility, some reactive functional groups have been incorporated into the molecular structure in order to afford materials with targeted properties. Aeronautical, electronic, and aerospace industries have focused on the use of these polymers as matrix systems due to their remarkable characteristics, such as: good thermal stability, high T g , long‐term dimensional stability, long‐term strength, low flammability, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–5 ] Polybenzoxazine precursors are synthesized via one stage Mannich‐like condensation from a phenol derivative, formaldehyde, and a primary amine in a stoichiometric molar ratio of 1:2:1. [ 6–9 ] As benzoxazine chemistry offers high molecular design flexibility, some reactive functional groups have been incorporated into the molecular structure in order to afford materials with targeted properties. Aeronautical, electronic, and aerospace industries have focused on the use of these polymers as matrix systems due to their remarkable characteristics, such as: good thermal stability, high T g , long‐term dimensional stability, long‐term strength, low flammability, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Aeronautical, electronic, and aerospace industries have focused on the use of these polymers as matrix systems due to their remarkable characteristics, such as: good thermal stability, high T g , long‐term dimensional stability, long‐term strength, low flammability, among others. [ 9–18 ] In particular, siloxane‐based polybenzoxazines have gained prominence due to their excellent thermal resistance and significant compatibility with organic compounds. [ 13,19–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[21] Among the numerous benzoxazines developed, those derived from bisphenol A are the most investigated. [22][23][24][25][26] In this sense, functional groups such as phosphates, phosphine oxides, and silicon have been incorporated into their chemical structures in order to increase the fire performance of the final materials. [27][28][29][30][31][32][33][34][35] According to previous studies it could be concluded that the most effective systems to improve flame retardant properties are those based on phosphorous.…”
Section: Introductionmentioning
confidence: 99%
“…Although benzoxazine resin has various advantages as described above, it needs to be modified to broaden its range of applications. There are two main strategies for modification of benzoxazines: (1) selection of different phenolics and amines to alter the performance of benzoxazine resin and (2) preparation of composite materials by blending or copolymerizing with other materials …”
Section: Introductionmentioning
confidence: 99%
“…There are two main strategies for modification of benzoxazines: (1) selection of different phenolics and amines to alter the performance of benzoxazine resin and (2) preparation of composite materials by blending or copolymerizing with other materials. [19][20][21][22][23][24][25][26] However, most of the raw materials used for the synthesis of benzoxazine are derived from petroleum resources. To protect the environment and mitigate the depletion of petroleum resources, the use of renewable resources has become an important topic in various fields.…”
Section: Introductionmentioning
confidence: 99%